On valuing biopharmaceutical product pipelines: An effectuation model and evidence - Mark J. Ahn; Anne S. York; Wei Wu; Yulianto Suharto; Tugrul Daim (Journal of Innovation and Entrepreneurship, 2015)
New creative approaches are needed to manage emerging biotechnology innovations, regulations, and payor environments to enhance product pipeline productivity, valuation, and risk management. Biopharmaceutical firms must make dynamic resource allocation decisions on their relative levels of internal R&D and external strategic alliances in furthering their pipelines. As the predominant method of using discounted cash flow (DCF) methodologies may lead to chronic underinvestment and performance, we evaluated the integration of traditional DCF with an effectuation model of analysis. Unlike traditional financial models that begin with the end goal of assumed known cash flows and recursively solve for portfolio optimization, the effectuation model-means, affordable loss, partnerships, and expect the unexpected-begins with resources that are readily available to the firm and then seeks to maintain strategic flexibility to take advantage of environmental contingencies as they arise. Using effectuation principles can provide insight into optimizing pipeline decisions by focusing on the logic of control rather than the logic of prediction. Using empirical data, we found that investors were able to effectively differentiate between the pipeline values of among companies. Overall, these results suggest that the integration of effectuation and DCF provides a lens from which to explore emerging varieties of small and large company innovation in the biopharmaceutical industry.
Keywords: 650